Territory, Economy, Society and Institutions in Transition. Keynote Speech presented at the 2019 AESOP Congress “Planning for Transition” in Venice. - Balducci, Alessandro (Taylor & Francis, 2020)
The keynote tries to interpret the transition that confronts planning by looking at economic, social, urban and institutional change. There are abundant studies that analyse transformations of territory, economy, society and institutions separately, but far fewer studies that allow us to consider the relationships between the profound processes of change that affect each of these systems, and their mutual influences. It approaches this issue by trying to understand die directions of causal relationships and how we can intervene to improve the policies that concern them, looking in particular at die role of the physical space and opens with an initial consideration drawn from Willem Salet's comments in an informal seminar: "The economy and society change with increasing speed, the physical space is hardly adapted to these changes, producing resistance and reconfiguring itself, the institutions adapt with even greater effort". The keynote addresses the transformation processes of the European city from Italy and in particular from Milan.
Keywords: Stadtplanung; Transformation; Strukturwandel; Wirtschaft; Sozialer Wandel; Raumbezogenheit; Stadtraum; Europäische Stadt